The Key role of MRI modalities in En Plaque Meningioma - Novita Tirtaprawita; Wiradharma Wiradharma; Julius July (Medicinus, 2018)
En plaque meningioma is at frontal region is difficult to be differentiated from osteoma, based on CT scan only. En plaque meningioma represents in 2-9% of all meningioma cases. Usually en plaque meningioma grows on the sphenoid wing, whereas only 1 % grows on the frontal and temporal bone. This case is female 37 year- old who presents with chronic headache and huge lump on her right forehead that she believes it slowly enlarges for the last 5 years. The Computerized Tomography scan (CT scan) shows thickening of the right fronto-temporal bone (3-4 cm) with the diameter of 12 cm and bony hard. Initial impression suggests it could be osteoma or fibrous dysplasia. After the MRI (Magnetic Resonance Imaging) with contrast, it shows a carpet like tumor underline the thickening bone, and it suggest an en plaque meningioma. For en plaque meningioma, we have to remove the abnormal duramater. We suggest that for a case with a wide thickening calvarian bone, it’s better to get the MRI of the head with contrast.